2021
DOI: 10.3390/plants10122736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant and Antibacterial Activities of White Mulberry (Morus alba L.) Fruit Extracts

Abstract: The fruit of mulberry trees (Morus sp.), mulberries, are traditionally utilised as a nutritional food and provide health benefits as well as skin nourishment in Thailand. White mulberries (Morus alba L.) from Chiang Mai and Mae Hong Son provinces were evaluated for their antioxidant and antibacterial activities. The antioxidant activities as well as the total phenolic, flavonoid and anthocyanin content of the aqueous and ethanolic extracts were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azinob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…These were 0.5 mg/mL when the white mulberry extract was tested and 0.25 mg/mL for the red raspberry extract. In contrast, the methanolic extract of wild raspberry leaves from the Balkan region and aqueous mulberry extracts from Mae Hong Son were the most effective against E. coli ATCC 8739 [38,73].…”
Section: Antibacterial Activitymentioning
confidence: 84%
“…These were 0.5 mg/mL when the white mulberry extract was tested and 0.25 mg/mL for the red raspberry extract. In contrast, the methanolic extract of wild raspberry leaves from the Balkan region and aqueous mulberry extracts from Mae Hong Son were the most effective against E. coli ATCC 8739 [38,73].…”
Section: Antibacterial Activitymentioning
confidence: 84%
“…Subjecting the bacteria to a concentration of 0.5 MIC at 6 time points (2, 4, 8, 12, 20, and 24 h) did not reduce the CFU counts of S. aureus even after 24 h (Pang et al, 2019). The mulberry fruit extracts had certain bactericidal activity against S. aureus ATCC 25923, taking 24 h to kill the bacteria (Suriyaprom et al, 2021). However, other research has reported the separation of specific substances from mulberries that show positive results against tested pathogens by the time-kill assay.…”
Section: Antibacterial Activity By the Time-kill Kinetic Methodsmentioning
confidence: 91%
“…Various biological properties of different mulberry extracts have been investigated and reported including medicinal potentials such as anti-cancer activity [ 52 ], anti-bacterial activity, and antioxidant activity [ 53 ]. Importantly, their toxicity needs to be assessed concurrently for a safe application.…”
Section: Discussionmentioning
confidence: 99%